2012
DOI: 10.1007/s10965-012-9854-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol and isopropanol on the structures and properties of polyethersulfone/perfluorosulfonic acid nanofibers fabricated via electrospinning

Abstract: Blend solutions of polyethersulfone (PES) and perfluorosulfonic acid (PFSA) resin were fabricated into nanofibers via electrospinning. Ethanol (EtOH) and isopropanol (IPA) were employed to investigate the effects of nonsolvent (NS) on the structures and properties of the electrospun PES/PFSA nanofibers. Average diameters of the electrospun nanofibers increased with NS content while the water contact angles of the nanofiber membranes decreased. Although all the nanofiber membranes presented strong hydrophobicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The PFSA/PVA NF mats exhibited good catalytic activity in ethyl acetate synthesis, with an efficiency proportional to the specific surface area of the NFs mats. The addition of the non-solvent to the electrospinning solution further improved the utilization of sulfonic acid groups in PFSA molecules [ 47 ]. Moreover, addition of nanoparticles [ 48 , 49 ] also improved the density of surface acid sites.…”
Section: Applications Of Nanofiber-based Iemsmentioning
confidence: 99%
“…The PFSA/PVA NF mats exhibited good catalytic activity in ethyl acetate synthesis, with an efficiency proportional to the specific surface area of the NFs mats. The addition of the non-solvent to the electrospinning solution further improved the utilization of sulfonic acid groups in PFSA molecules [ 47 ]. Moreover, addition of nanoparticles [ 48 , 49 ] also improved the density of surface acid sites.…”
Section: Applications Of Nanofiber-based Iemsmentioning
confidence: 99%
“…However, it is difficult to obtain nanofibers by the electrospinning of Nafion solutions due to the low solution viscosities resulting from the poor entanglement of the polymer chains and the presence of aggregates in the solution due to ionic interactions . To solve this problem, it has been common to add small amounts of spinning aids, such as poly( N ‐vinyl pyrrolidone), poly(ethylene oxide), poly(acrylic acid), poly(vinyl alcohol), poly(ethersulfone), and poly(acrylonitrile), to the Nafion solutions to increase the polymer chain entanglement or to suppress the aggregation formation. Subianto et al reported that the threshold concentration of poly(ethylene oxide) for fiber formation depends on both the molecular weight of poly(ethylene oxide) and the concentration of the perfluorosulfonic acid ionomers .…”
Section: Applications Of Ion‐exchange Nanofibersmentioning
confidence: 99%
“…PES also exhibits high mechanical strength, thermo-stability and stability against chemicals [4] which make it very good candidate for fabrication of gas separation membranes [5][6][7]. Several studies have focused on modification of PES membranes to expand its applications in gas separation industries.…”
Section: Introductionmentioning
confidence: 99%